1983
DOI: 10.1002/jlac.198319831105
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Coumarins. ‐ Nucleophilic Substitutions of 4‐Chloro‐3‐nitrocoumarin with Hard and Soft Nucleophiles

Abstract: Reactions of 4-chloro-3-nitrocoumarin with a variety of nucleophiles produced a number of novel substituted coumarins. Hard and borderline nucleophiles exclusively substitute chlorine in position 4, while soft nucleophiles substitute the nitro group in position 3 (except for iodide) of the title compound. This result of the nucleophilic substitution of 4-chloro-3-nitrocoumarin is rationalized in terms of the HSAB model. Chemie der Cumarine. -Nucleophile Substitutionen an 4-Chlor-3-nitrocumarin mit harten und w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Based on the »hard and so (Lewis) acids and bases« (HSAB) concept that electrophiles a ack the coumarine ring (19), the eight heterocyclic amines, isoxazoles and thiazoles, were derivatized to obtain diazonium ions which would be further used as electrophiles to a ack the coumarine ring at position 3. Isoxazole and thiazole substituents were used based on the literature data pointing to the antiproliferative and tumour vascular-disrupting activity of their derivatives (20)(21)(22)(23), with isoxazole and thiazole rings being important pharmacophores.…”
mentioning
confidence: 99%
“…Based on the »hard and so (Lewis) acids and bases« (HSAB) concept that electrophiles a ack the coumarine ring (19), the eight heterocyclic amines, isoxazoles and thiazoles, were derivatized to obtain diazonium ions which would be further used as electrophiles to a ack the coumarine ring at position 3. Isoxazole and thiazole substituents were used based on the literature data pointing to the antiproliferative and tumour vascular-disrupting activity of their derivatives (20)(21)(22)(23), with isoxazole and thiazole rings being important pharmacophores.…”
mentioning
confidence: 99%
“…HRMS(EI): M + (C16H12N2O4) 296.0815, requires 296.0797 (= +1.8 mmu). IR and 1 H and 13 C NMR (in CDCl3) previously published (Tabaković et al, 1983;Dekić et al, 2010c 2H, H-6, H-8), 7.00-7.20 (m, 4H, H-2', H-3', H-5', H-6'), 2.31 (s, 3H, CH3).…”
Section: -[(4-methylphenyl)amino]-3-nitro-2h-chromen-2-one (5f)mentioning
confidence: 79%
“…25 %) (Scheme 2). Modification of this step was based on the report that the chlorine atom at position 4 cannot be attacked by water [29]. Also, it was found that in general the sulfonyl chlorides are insoluble and stable in water [31].…”
Section: Resultsmentioning
confidence: 99%
“…Based on these facts we wanted to combine the coumarinic system with 1,2,4-thiadiazines in the hope that the resulting novel heterocycles would be biologically active, especially as anticancer and anti-HIV agents. Also, we designated positions 3 and 4 of coumarin for annellation, because these positions are mainly attacked by electrophiles and nucleophiles, respectively [29].…”
Section: Introductionmentioning
confidence: 99%